Sami Pihlström, Friedrich Stadler, Niels Weidtmann (eds.), Logical Empiricism and Pragmatism (Dordrecht: Springer, 2017). - Gori, Pietro (Philosophical Readings, 2020)
Review of the collective volume on "Logical Empiricism and Pragmatism" published in the Vienna Circle Institute Yearbook series, Springer.